2017
DOI: 10.1186/s12916-017-0839-z
|View full text |Cite
|
Sign up to set email alerts
|

Daily home fortification with iron as ferrous fumarate versus NaFeEDTA: a randomised, placebo-controlled, non-inferiority trial in Kenyan children

Abstract: BackgroundWe aimed to show the non-inferiority of home fortification with a daily dose of 3 mg iron in the form of iron as ferric sodium ethylenediaminetetraacetate (NaFeEDTA) compared with 12.5 mg iron as encapsulated ferrous fumarate in Kenyan children aged 12–36 months. In addition, we updated a recent meta-analysis to assess the efficacy of home fortification with iron-containing powders, with a view to examining diversity in trial results.MethodsWe gave chemoprevention by dihydroartemisinin-piperaquine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Our meta-analysis suggested a small gain in haemoglobin concentration in most trials, indicating that point-of-use fortification with iron-containing micronutrient powders provides some benefit across different settings [ 2 ]. On average, in an arbitrarily selected setting, and with an adherence as obtained under trial conditions, one may expect an increase in haemoglobin concentration by only 3.9 g/L, with the upper limit of the 95% CI virtually excluding an effect beyond 5.5 g/L; the attenuated effect that is likely to be achieved under real-world conditions is even lower.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our meta-analysis suggested a small gain in haemoglobin concentration in most trials, indicating that point-of-use fortification with iron-containing micronutrient powders provides some benefit across different settings [ 2 ]. On average, in an arbitrarily selected setting, and with an adherence as obtained under trial conditions, one may expect an increase in haemoglobin concentration by only 3.9 g/L, with the upper limit of the 95% CI virtually excluding an effect beyond 5.5 g/L; the attenuated effect that is likely to be achieved under real-world conditions is even lower.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…In a recent placebo-controlled trial among Kenyan children aged 12–36 months, we found no evidence that daily point-of-use fortification with either 3 mg iron as NaFeEDTA or 12.5 mg iron as ferrous fumarate was efficacious in improving haemoglobin concentration or plasma iron markers [ 2 ]. As discussed in a commentary [ 3 ], the decline in anaemia prevalence over time that we observed in all intervention groups may have been due to premedication with anti-malarial and anti-helminth medication at baseline, or due to the vitamin A or zinc content in the fortification powders.…”
Section: Introductionmentioning
confidence: 99%
“…Although nutritional deficiencies (like VAD), hookworm infection, and haemoglobinopathies [17,18] may predispose children to the development of anaemia, evidence suggests that, malaria is one of the most important factors [16]. Other predisposing factors include increased pathogenic profile in the gut, inflammations, inhibitory food compounds and infections [19,20]. Ghanaian school children are confronted with adverse effect of anaemia: low physical activity and low attention span, which can lead to poor academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…The basis of this recommendation was a meta-analysis of randomised controlled trials showing moderate quality evidence for an effect on anaemia and haemoglobin concentration [ 2 ]. In a recent placebo-controlled trial, however, we failed to find effects of home fortification with iron-containing micronutrient powders on either anaemia or haemoglobin concentration [ 3 ]. In addition, in an updated meta-analysis, we showed that the magnitude of the effect on haemoglobin concentration varied between trials [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent placebo-controlled trial, however, we failed to find effects of home fortification with iron-containing micronutrient powders on either anaemia or haemoglobin concentration [ 3 ]. In addition, in an updated meta-analysis, we showed that the magnitude of the effect on haemoglobin concentration varied between trials [ 3 ]. Such variability in trial results may be due in part to population differences in adherence to home fortification.…”
Section: Introductionmentioning
confidence: 99%